Histopathological analysis in Litopenaeus vannamei infected with Vibrio parahaemolyticus. - Peña-Navarro, Nelson (2015)
The objective of this work was to describe the main histopathological results obtained from the different immune responses in L. vannamei after infection induced with V. parahaemolyticus. Inoculation bacterial was conducted in the Research Center for Ocean Sciences and Limnology at the University of Costa Rica betwen june to august 2011. The research used 40 shrimp of farms located in the Nicoyan Peninsula; each was injected an average of 2,0x106 CFU of V. parahaemolyticus. At the end of the period of infection, histopathological analysis were conducted on gills, subcuticular epithelium, hepatopancreas, intestine, gut lymphoid organ, hematopoietic tissue, striated muscle, nervous tissue, heart, among others. The main histological findings were melanized hemocytes, haemocyte infiltration, melanosis, spheroids type A, B and C, coagulative myonecrosis, pyknosis, among others, useful to determining in the health status of shrimp in particular, cytopathic effect of V. parahaemoltycus in systemic infections.